Paediatric acute asthma management in Australia and New Zealand: practice patterns in the context of clinical practice guidelines. Issue 4 (20th March 2008) - Babl, F E; Sheriff, N; Borland, M; Acworth, J; Neutze, J; Krieser, D; Ngo, P; Schutz, J; Thomson, F; Cotterell, E; Jamison, S; Francis, P
Abstract : Objectives: To compare clinical practice guideline (CPG) recommendations and reported physician management of acute paediatric asthma in the 11 largest paediatric emergency departments, all of which have CPGs, in Australia (n = 9) and New Zealand (n = 2). All 11 sites participate in the Paediatric Research in Emergency Departments International Collaborative (PREDICT) research network. Methods: ( a ) A review of CPGs for acute childhood asthma from all PREDICT sites. ( b ) A standardised anonymous survey of senior emergency doctors at PREDICT sites investigating management of acute childhood asthma. Results: CPGs for mild to moderate asthma were similar across sites and based on salbutamol delivery by metered dose inhaler with spacer and oral prednisolone. In severe to critical asthma, differences between sites were common and related to recommendations for: ipratropium use; metered-dose inhaler versus nebulised delivery of salbutamol in severe asthma; use of intravenous aminophylline, intravenous magnesium and dosing of intravenous salbutamol in critical asthma. The questionnaire (78 of 83 doctors responded) also revealed significant differences between doctors in the treatment of moderate to severe asthma. Ipratropium was used for moderate asthma by 42%. For severe to critical asthma, nebulised delivery of salbutamol was preferred by 79% of doctors over metered dose inhalers. For critical asthma, doctors reported using intravenous aminophylline in 45%, intravenous magnesium in 55%, and intravenous salbutamol in 87% of cases. Thirty-nine different dosing regimens for intravenous salbutamol were reported. Conclusions: CPG recommendations and reported physician practice for mild to moderate paediatric asthma management were broadly similar across PREDICT sites and consistent with national guidelines. Practice was highly variable for severe to critical asthma and probably reflects limitations of available evidence. Areas of controversy, in particular the comparative efficacy of intravenous bronchodilators, would benefit from multi-centre trials. Collaborative development of CPGs should be considered.